A Jew in the Roman Bathhouse : Cultural Interaction in the Ancient Mediterranean - Eliav, Yaron Z. (Book collections on Project MUSE., 2023)
"This monograph argues that Roman bathhouses were laboratories in which Jews interacted with Graeco-Roman culture. It tells the story of the Jews who frequented them, documenting their pleasures, anxieties, and concerns, and reconstructing their thoughts, feelings, and beliefs about the activities that took place there. The chapters of the book are arranged as an invitation to follow the ancient Jew as he or she engages the bath, and highlights details small and large about what Jews knew about the place, but even more so, about what they felt about it. Were they intimidated by the nudity that prevailed there or by the sculptures that adorned the place? How did Jewish law configure the bath? What were the Jewish social norms that developed there? Exploring these questions enhances and complicates our understanding of ancient Judaism and its encounter with the dominant way of life around it. Jewish engagement with and perceptions of the bathhouse are documented in numerous sources: inscriptions on stone, documents written on papyri, and most of all, in hundreds of references in the Jewish literature of the time. These stories, laws, and regulations, written in Greek, Aramaic, and Hebrew, reflect every aspect of Jewish life in the ancient Mediterranean. In this monograph, Yaron Eliav brings all of these sources together for the first time"--